Study Analysis: Learning Pattern of Blind Children Using Aid Applications for Science Learning - Akhmad, Nur Amaliah; Mania, Sitti; Marjuni, Marjuni; Rasyid, Muhammad Nur Akbar (PT. Riset Press International, 2024)
Use of technology for learning for blind children. One of the main gaps is the availability and accessibility of this technology in the school environment. Not all schools have adequate infrastructure or financial support to implement technology effectively. This research uses a descriptive qualitative approach with triangulation techniques in data collection to provide an in-depth description of the learning process evaluation for blind students at SLB 1 Makassar. The data collection technique involved four blind students and four teachers who were also blind, selected through purposive sampling. The Context, Input, Process, Product (CIPP) approach developed by Stufflebeam was used as the framework. This research focuses specifically on evaluating the learning process. Unique dynamics in the blind class at SLB 1 Makassar, where teachers and students face blind disabilities. The presence of teachers who are also blind, especially those with total blindness, creates a learning environment full of empathy and mutual understanding. The Be My Eyes, Voice Dream Reader, and Blind Square applications contribute significantly to the inclusive education of blind children at SLB 1 Makassar. With the help of this application, it is possible to increase the independence of blind children in learning, especially science learning.